Protótipo de programa de computador para monitoramento de depósito de patentes a partir da base do INPI - Lima, Edilson Ponciano de (2019)
Intellectual property is splitted among copyright, industrial property and Sui Generis protection. Other industrial properties include one of the most important sources of technological information, the patent. Monitoring patent documents can provide useful information for researchers and investors. The increasing volume of filings and requests for this type of intellectual property protection made tracking and searching for information in the national patent base a not fast and efficient task, given as restrictions and inconsistencies of the National Industrial Property Institute's - INPI search engine. The objective of this research was to develop a computer program prototype for monitoring customer deposits at the INPI base. To this end, process models were developed in BPMN notation and the Design Thinking methodology was applied in the development of the computer program prototype. The developed program is able to perform the monitoring, search and classification of information contained in the Magazine of Industrial Property - RPI, which is the official means of publication of Intellectual Property subjects in Brazil. The prototype of the computer program was registered at the INPI. The program source code and process model diagrams are shared in an open repository to provide inputs for collaboratively creation of new products for innovation